Asperula calabra (Rubiaceae) and allied taxa in southern Apennines, Italy. (4th March 2017) - Del Guacchio, E.; Gargiulo, R.; Caputo, P.
Abstract: The present work is aimed at studying several Asperula (Rubiaceae) sect. Cynanchicae populations in southern Apennines, Italy, with particular reference to those referred to A. calabra, by employing biometrical methods on macromorphological data. Among other historical misapplications, A. cynanchica subsp. cynanchica seems to be very rare or missing in southern Italy. The enigmatic Asperula calabra, confirmed to be limited to a single mountain population in Calabria, appears to be strictly related to A. aristata subsp. scabra, so we suggest to treat it as a further subspecies of A. aristata . This latter species is otherwise distributed throughout southern Italy with subsp. scabra and subsp. aristata, characterised by slight morphological differences, which are correlated to altitudinal ranges.